Patient Safety Culture Analysis at Sultan Agung Islamic Dental Hospital to Improve Patient Safety - Kusuma Arbianti; Rosa Amalia; Julita Hendrartini; Tjahjono Kuntjoro; Gesti Bening Aulia; Ghea Tri Khusnul Khotimah (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
A culture of patient safety can improve hospital patient safety. Patient safety is the foundation of quality health services, an indicator of assessment in healthcare facilities, and a mechanism by which health services protect patients from harm. The purpose of this study is to examine the patient safety culture at Sultan Agung Islamic Dental Teaching Hospital Semarang in order to identify ways to improve patient safety. A cross-sectional research of 124 participants was conducted at Sultan Agung Dental Teaching Hospital, Semarang, Indonesia. Distributing questionnaires to collect data, the Dental Office Survey on Patient Safety Culture (DOSOPSC) includes 58 items and 10 dimensions. Out of a total of 124 respondents, the average positive response value exceeded the dependability criterion on four dimensions: teamwork (93.7%), the highest, and work pressure and speed (56.2%), the lowest. There are four areas in which the average positive response value exceeds the dependability threshold, including teamwork, staff training, hospital systems and standards, work pressure, and speed.